ANALISA KOORDINASI, KOMUNIKASI DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI SEKRETARIAT DPRD KOTA TANGERANG - Irma Darmawati; Priyo Susilo (JMB : Jurnal Manajemen dan Bisnis, 2019)
The purpose of this study was conducted to determine the effect of communication, communication and social performance on the Tangerang City DPRD Secretariat. The research method used is survey research method. P The population of this study is all employees of the Tangerang City DPRD Secretariat totaling 60 people. The sampling technique uses saturated sampling techniques from the total population of 60 people, so the research sample is taken. The number of samples in this study was 60 people. Data analysis using Multiple Linear Regression Analysis. Based on the results of the study indicate that: There is a positive and significant effect of coordination on employee performance at the Tangerang City DPRD Secretariat. This means that the better coordination will improve employee performance, and vice versa, the worse the coordination will have an impact on employee performance. There is a positive and significant influence of communication on employee performance at the Tangerang City DPRD Secretariat. This means that the better the communication will improve employee performance, and vice versa the worse the communication will have an impact on the low performance of employees.There is a positive and significant influence of organizational culture on employee performance. at the Tangerang City DPRD Secretariat. This means that the better the organizational culture will improve employee performance, and vice versa the worse the employee's organizational culture will have an impact on the low performance of employees.There is an influence of coordination, communication and organizational culture together on employee performance at the Tangerang City DPRD Secretariat. This means that good coordination, communication and organizational culture will affect the improvement of employee performance, and vice versa, poor coordination, communication and organizational culture will have an impact on the low performance of employees